2020
DOI: 10.24836/es.v30i56.986
|View full text |Cite
|
Sign up to set email alerts
|

Dinámicas obesogénicas de escolares de la zona metropolitana de Zacatecas-Guadalupe

Abstract: Objetivo: comparar las características de las dinámicas obesogénicas de escolares de la zona metropolitana Zacatecas-Guadalupe de acuerdo con su condición sociodemográfica: zona de alta prioridad social y zona de no alta prioridad social. Metodología: estudio transversal, comparativo, cuantitativo, descriptivo y socioespacial. Bajo un muestreo por cuotas se seleccionaron diez escuelas primarias públicas por zona para analizar indicadores del ambiente obesogénico alrededor de las mismas. Se consideró la cantida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the LAC region, it has been observed that the trends in increasing food insecurity and overweight–obesity are related to populations in marginalized areas, women, farmers, Indigenous Peoples, and rural areas [ 2 , 12 ]. It is important to emphasize that while social programs have been implemented to address food security and reduce malnutrition, they have tended to focus primarily on combating child malnutrition and hunger, especially since the impacts of the 2008 food and financial crisis [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the LAC region, it has been observed that the trends in increasing food insecurity and overweight–obesity are related to populations in marginalized areas, women, farmers, Indigenous Peoples, and rural areas [ 2 , 12 ]. It is important to emphasize that while social programs have been implemented to address food security and reduce malnutrition, they have tended to focus primarily on combating child malnutrition and hunger, especially since the impacts of the 2008 food and financial crisis [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%